Knowledge and perception about HPV in the university population in Brazil: an integrative review (Research, Society and Development, 2022)
Objective: To identify the scientific evidence available in the literature about the knowledge and perception of HPV in the university population in Brazil. Methods: this is an Integrative Literature Review, which followed the PICO strategy, the studies analyzed were obtained in electronic databases LILACS, MEDLINE, BDENF, CINAHL and SciELO, using the PRISMA method. We considered free articles, original with full text, considering the period from 2012 to 2022 in English, Spanish and Portuguese. Results: the crossings in the databases resulted in 47 items of which 11 were selected to be part of the study after full reading all. The results found in this review reveal that, although many of the academics have demonstrated knowledge about what HPV is, several knowledge gaps were identified, such as its relationship with cervical cancer and other types of cancer, its symptoms, transmissibility, risk factors for infection and vaccine issues, such as number of doses, target audience, risks and benefits. Conclusion: it is necessary to guide educational actions and health promotion practices in the university environment regarding HPV, since it is the environment in which professionals are trained that has the responsibility to transmit information to the population.